2014
DOI: 10.2139/ssrn.2427653
|View full text |Cite
|
Sign up to set email alerts
|

Individual Heterogeneity, Nonlinear Budget Sets, and Taxable Income

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 72 publications
2
29
0
Order By: Relevance
“…Blomquist and Newey (2002) used variation in budget sets to nonparametrically estimate the average labor supply effect of the Swedish tax reform of 1990-1991 for scalar heterogeneity, with optimization errors. Blomquist et al (2015) showed that these results are valid with general heterogeneity and demonstrated how to impose all the restrictions of utility maximization in estimating average labor supply. Manski (2014), and Kline and Tartari (2016) nonparametrically identified and estimated bounds on important effects, without allowing for optimization errors.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Blomquist and Newey (2002) used variation in budget sets to nonparametrically estimate the average labor supply effect of the Swedish tax reform of 1990-1991 for scalar heterogeneity, with optimization errors. Blomquist et al (2015) showed that these results are valid with general heterogeneity and demonstrated how to impose all the restrictions of utility maximization in estimating average labor supply. Manski (2014), and Kline and Tartari (2016) nonparametrically identified and estimated bounds on important effects, without allowing for optimization errors.…”
Section: Introductionmentioning
confidence: 78%
“…We note that this result allows for general heterogeneity where the dimension of  is unknown. A more general version of this result was given in Blomquist et al (2015) and is now given in the Appendix of this paper. We will use this result to characterize kink probabilities in terms of compensated elasticities.…”
Section: Nonparametrics With General Heterogeneitymentioning
confidence: 96%
See 2 more Smart Citations
“…This is essentially an under-identification problem, which is more formally characterized by Blomquist et al (2015), who emphasize the need for additional moments in the data that would allow us to select among models. The subsequent bunching literature has broadly pursued two main strategies for handling this identification issue.…”
Section: Introductionmentioning
confidence: 99%